Géopolitique africaine et rébellions touarègues. Approches locales, approches globales (1960-2011) - Pierre Boilley (L’Année du Maghreb)
The Tuareg situation epitomized by rebellions since the 1960s has generally been considered as a major problem, limited however to the Sahel and southern Sahara. Current developments in the region of drug trafficking and settlement of armed Salafists of Al-Qaeda in Islamic Maghreb (AQIM), have brutally internationalized the interest shown in the issue. However, since the revolt of 1963-64, the Tuaregs have always had to deal with policies beyond their own interests and African and global geostrategies with multiple actors and interests. By analyzing the facts we were able to place these realities back in their contexts and better understand the progress and failures of these struggles. Local approaches must give way to comprehensive approaches.